Impact of Nicotine and Nicotine-Free E-Cigarettes on Body Weight, Erythrocyte Dynamics, Sperm Morphology, and Molecular Outcomes in Mice - Mandasari, Andita Ayu; Maryam, Siti Ayu; Firdausi, Chilyatul; Maulana, Muhammad Iqbal; Kurnia, Muhammad Hardi; Widyastuti, Dyah Ayu; Herawati, Dheasy (Bogor Agricultural University, Indonesia, 2025)
The effect of electric cigarettes (e-cigs) on health should be a concern since their legality has occurred in Indonesia. Young adults use e-cigarettes not as therapy but as a lifestyle. The vapor component contains propylene glycol, vegetable glycerin, flavor, and nicotine, which may harm human health. This study examined the health risks of e-cigarettes on body weight, erythrocytes, and sperm morphology in mice. We used twenty healthy male mice exposed to the cigarette's vapor for thirty days. Mice were divided into room air as the negative control, nicotine-free, and 18 mg nicotine-containing groups. Our results showed that the body weight of the nicotine-free and nicotine-containing groups increased, while micronuclei formation increased after e-cig exposure. Furthermore, abnormal sperm morphology in the nicotine-containing groups increased significantly, yet the nicotine-free group was not significantly different compared to the negative control. These results were supported by the molecular prediction that exposure to e-cigs might increase oxidative stress and decrease the expression of TGF-β. Moreover, studies on it are ongoing to gather scientific evidence.